The path to God is through the heart: Metaphoric self-location as a predictor of religiosity. Issue 6 (17th August 2020) - Fetterman, Adam K.; Juhl, Jacob; Meier, Brian P.; Abeyta, Andrew; Routledge, Clay; Robinson, Michael D.
ABSTRACT: Metaphors linking the heart to warm intuition and the head to cold rationality may capture important differences between people because some locate the self in the heart and others locate the self in the head. Five studies (total N = 2575) link these individual differences to religious beliefs. Study 1 found that religious beliefs were stronger among heart-locators than head-locators. Studies 2 and 3 replicated this relationship in more diverse samples. Studies 4 and 5 focused on questions of mediation. Heart-locators believed in God to a greater extent partly because of empathy-related processes (Study 4) and partly because they tended to think in less analytic terms (Study 5). These studies extend our knowledge of how metaphors interact with personality processes.